2004
DOI: 10.1191/1352458504ms1077oa
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA on progression of optic neuritis to multiple sclerosis: results of a four-year follow-up study

Abstract: The study strongly suggests the association among DR2, A23 and B21 allele and the evolution of ON to MS. High prevalence of A23 and DR2 alleles in CDMS patients compared with the normal population may suggest an important role for these alleles in the development of MS. The study suggests B51 as a protective factor against development of ON in the normal population. In addition, results do not confirm previous studies considering A11 as a predisposing factor. The present study finally evokes that different cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Notably, in contrast to HLA-A3, other members of the A3 superfamily (HLA-A11, HLA-A3301, HLA-A3101 and HLA-Aw*6801), which by definition share peptide-binding properties with HLA-A3, do not appear to be associated with MS (Harbo et al, 2004;Kheradvar et al, 2004). A report of a modest predisposing effect of HLA-A11 in the Indian popu-lation was tempered by the particular small sample group studied (Kankonkar et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Notably, in contrast to HLA-A3, other members of the A3 superfamily (HLA-A11, HLA-A3301, HLA-A3101 and HLA-Aw*6801), which by definition share peptide-binding properties with HLA-A3, do not appear to be associated with MS (Harbo et al, 2004;Kheradvar et al, 2004). A report of a modest predisposing effect of HLA-A11 in the Indian popu-lation was tempered by the particular small sample group studied (Kankonkar et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Several studies have suggested that HLA-B51, HLA-DR, and HLA-A11 may be protective in patients with ON against progression to MS [21,22]. The data on HLA-A11 have been difficult to replicate in some studies [23].…”
Section: Pathology and Immunologymentioning
confidence: 99%
“…A number of factors explain the link between ON and MS. These factors include abnormal cerebrospinal fluid (CSF) at the onset of ON (Sandberg-Wollheim et al 1990;Klistorner et al 2009), certain human leukocytes antigen (HLA) types (Frith et al 2000;Kheradvar et al 2004), and brain magnetic resonance imaging (MRI) lesions, which are frequently present in patients with ON (Jin et al 2003;Optic Neuritis Study Group 2008). A recent study indicated that Tau protein may be a possible prognostic factor in ON and MS (Frederiksen et al 2012).…”
Section: Introductionmentioning
confidence: 99%